In‐Situ Oxygen‐Evolving Photoactive Nanococktail: The Future of Hypoxic Tumour Photodynamic Therapy. (19th July 2019) - Banerjee, Samya
Abstract : Hypoxia‐related resistance is one of the main challenges for photodynamic therapy to overcome. This highlight discusses a few current works on possible ways to overcome this problem by in situ oxygen generation in the hypoxic core of tumours.